4. Case Study: Gallstones (Cholelithiasis) in Long-tailed Macaques (Macaca fascicularis) - J. Susilo; B. Tri Wibowo; Y. Tinasari; M. Nur Salim; Dian Masyitha; Erdiansyah Rahmi; M. Isa; Herialfian Herialfian; Fakhrurrazi Fakhrurrazi; T. Fadrial Karmil; Fadli A. Gani (Jurnal Medika Veterinaria, 2021)
The purpose of this case study is to diagnose the cause of death of the long-tailed macaque (Macaca fascicularis). Two cadaver of Macaca fascicularis were received by the Lampung Veterinary Center from a customer. Necropsy was carried out at the Pathology Laboratory of the Lampung Veterinary Center by observing macroscopic changes. The samples taken were then observed by gram staining in the Bacteriology laboratory and hematoxylin-eosin staining at the Pathology laboratory. The results of macroscopic observations showed an enlarged gallbladder with a length of 4 cm and a width of 2 cm, blackish in color. Gallbladder surgery found 15 gallstones measuring 2 mm in diameter, brownish-colored bile, fibrin clots, and blood. The native gram stain of bile showed several types of rod-shaped bacteria form and gram-negative cocci (eosinophilic), and gram-positive rods (basophilic). Specific histopathological changes in the ductus choleductus are multifocal neutrophil inflammatory cell infiltration, enlarged gallbladder lumen filled with multi-bacterial, cell debris, fibrin, and erythrocytes. Multifocal hepatitis occurs by neutrophils, multibacterial, and fibrin. It can be concluded that the causes of death of Macaca fascicularis were cholelithiasis and hepatitis.